Factorization properties and generalization of multipliers in module actions - Kazem Haghnejad Azar (Journal of Hyperstructures, 2015)
In this paper, We establish some necessary and sufficient conditions for relationships between the topological centers of module actions and factorization properties of them and we give a new definition for multiplier in module actions with some results.